2020
DOI: 10.3988/jcn.2020.16.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of MRI Contrast Enhancement of the Oculomotor Nerve in Ischemic Isolated Oculomotor Nerve Palsy

Abstract: Background and Purpose Contrast enhancement of the oculomotor nerve in MRI was recently noticed in patients with clinical ischemic isolated oculomotor nerve palsy (iIONP). The opinions about whether this is a sign of inflammation and whether or not to administer steroids vary between doctors. The study aimed to determine the associations between this enhancement and vascular-disease risk factors (VRFs) and inflammatory factors in iIONP patients. Methods The study recruited patients who had experienced iIONP du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
16
0
3
Order By: Relevance
“…We and our colleagues found no statistical differences in improvement scores between patients with and those without 80 mg of methylprednisolone in addition to ­routine therapy [8]. Similar to the previous studies, >3 months were required for our patients to achieve complete restoration even with corticosteroid use.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We and our colleagues found no statistical differences in improvement scores between patients with and those without 80 mg of methylprednisolone in addition to ­routine therapy [8]. Similar to the previous studies, >3 months were required for our patients to achieve complete restoration even with corticosteroid use.…”
Section: Discussionsupporting
confidence: 78%
“…There were also no significant differences in the levels of HbAlc and fasting blood glucose between the enhancement group and nonenhancement group, which suggested that blood glucose levels were not a major risk factor for the development of cranial nerve enhancement. Among patients with ischemic ONP, our colleagues did not detect differences in the levels of some common plasmatic inflammatory factors such as erythrocyte sedimentation rate and C-reactive protein between patients with and those without the enhancement of the oculomotor nerve [8]. Two patients presented abnormal oligoclonal bands and intrathecal IgG synthesis, and it suggested that some other inflammatory components may accompany nerve enhancement in a hyperglycemia-independent manner [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only a few studies have reported findings suggestive of OCNPi. One study group showed enhancement of the third cranial nerve on thin-section MRI but did not confirm the same findings of the fourth or sixth cranial nerves, and further validation is needed 18 , 19 . WMH was associated with OCNPi regardless of the cranial nerve involved in this study.…”
Section: Discussionmentioning
confidence: 91%
“…If this condition is associated with GQ1b, there may be changes in CSF protein. Contrast-enhanced findings of the oculomotor nerve on MRI have been reported in diabetic oculomotor palsy and idiopathic oculomotor palsy (Zhao et al 2021 1 ; Yang et al 2020 2 ). This finding is not specific to MFS.…”
mentioning
confidence: 95%